A275 COMPREHENSIVE GENOMIC ANALYSIS RESULT IN EARLY DETECTION AND IMPLEMENTATION OF IMMUNE CHECK POINT THERAPY TO IMPROVE SURVIVAL FOR PATIENTS WITH INHERITED REPLICATION REPAIR DEFICIENCY GASTROINTESTINAL CANCERS:REPORT FROM THE INTERNATIONAL REPLICATION REPAIR CONSORTIUM. (15th March 2019) - Durno, C; Aronson, M; Edwards, M; Boufett, E; Tabori, U
Abstract: Background: Understanding tumor biology in patients with gastrointestinal cancers has implications for treatment. Replication repair deficiency (RRD) is a major contributor to carcinogenesis and is enriched in gastrointestinal (GI) malignancies. Germline mutations in the mismatch repair and DNA polymerase genes result in early onset RRD gastrointestinal cancers. In order to better understand RRD tumor biology, develop diagnostic tools, surveillance protocols and novel therapies, an international RRD consortium was established. Aims: The aim of the study is to explore diagnostic testing of GI tumors with replication deficiencies and impact clinical outcome. Methods: Patients referred to the International RRD Consortium undergo genetic testing to confirm Lynch Syndrome, Constitutional mismatch repair deficiency syndrome (CMMRD) or germline POLE mutations . Tumor analysis include Immunohistochemistry, microsatellite analysis and next generation sequencing. Clinical data are collected as part of the clinical surveillance protocol. Immune Check Point therapy (ICI) is offered to patients with recurrent metastatic tumors. Results: One hundred and forty-nine patients with RRD are registered in the consortium from 40 countries. These patients developed 225 malignancies. Fifty-seven GI cancers were diagnosed in 41 patients (79% colorectal cancer/20.5% small bowel/0.5% gastric cancer). Mean age at first GI cancer was 18.4 years (8.1 - 40.0 years). MSI testing are informative in 23% of patients with CMMRD and POLE mutations. IHC revealed lack of staining in 92% of the corresponding gene (p<0.0001). Tumor mutational burden revealed hypermutation in all cancers. Higher in tumors with both MMRD/POLE mutations. The addition of mutational signatures resulted in 100% sensitivity in detection of germline RRD. Surveillance protocol implemented in 65 individuals detected twenty-one gastrointestinal cancers. All patients are currently alive. Of 45 RRD patients treated with ICI, 9 had gastrointestinal cancers, most with relapsed metastatic disease. Overall survival at 2 years is 89%+/-10% which compared favorably with historical controls. Conclusions: Cancers are common in children and young adults with RRD. Tumor genomic analysis revealed hypermutation and unique tumor signatures which can identify patients who may benefit from targeted therapy with immune check point therapy. MSI testing, the hallmark of Lynch cancers was not sensitive or specific in all RRD tumors. Surveillance protocol and ICI therapy directed to gastrointestinal RRD result in improved survival. It is important to identify patients with inherited GI cancer predisposition syndromes as novel targeted therapy is available. Funding Agencies: The Zane Cohen Center,